Customer and Supplier Relationships and Their Characteristic in the Automotive - Morauszki, Kinga; Lajos, Attila (International Journal of Engineering and Management Sciences, 2016)
This article gives short review with the help of specialized literature that was written both national and overseas.This gives information about whatrelationships can you speak in the automotive.This study briefly presents what are the forms which are preferred by the companies, they are more general and what distinctive characteristics do the forms of contact have. Essential question of the customer-supplier relationships is the following – how does the customer company treat its supplier as a partner. The supplier relationship is very precious if we are not talking only about easy product-delivery but a positive relationship can be developed between the two sides. The aim of this study is a literature review which has summarized the theoretical ground of this subject, so that means a kind of a starting point in the practice.